Sentiment Analysis and Topic Modelling of The COVID-19 Vaccine in Indonesia on Twitter Social Media Using Word Embedding - Kartikasari Kusuma Agustiningsih; Ema Utami; Omar Muhamammad Altoumi Alsyaibani (Universitas Ahmad Dahlan, 2022)
This study aims to analyze the sentiments of the Indonesian people towards the COVID-19 vaccine on Twitter. Data collection was carried out from September 2020 to June 2021 with the keyword